Translations and Transcreations of Advertising Posts on Twitter and Instagram: Netflix in Spanish - García-Jiménez, Rocío; García-Aguiar, Livia Cristina (Íkala, Revista de Lenguaje y Cultura, 2022)
US-based Netflix has become one of the most powerful video streaming service around the world. Currently, social media, especially Twitter and Instagram, provide companies and brands like Netflix, a chance to reach their audience directly. This is why the company often uses these media for advertising purposes. This article aims to analyze translation strategies and transcreations used by Netflix in their Twitter and Instagram accounts in Spanish, and to compare both versions to assess some potential differences on the strategies used. To do that, 26 messages posted in both social media throughout the first half of 2018, were taken and descriptively analyzed. The results suggest that the translation strategies used in Spain are different from those used in their Latin profile, which resort more often to transcreation. Also, we noticed that while Twitter is preferred to launch new products, Instagram is used as a means to establish them among their audience.
Keywords: Traducción; Redes sociales en Internet; Advertising; Instagram; Netflix; Translation; Twitter; Transcreations; Social media